A CLINICAL STUDY ON IRON DEFICIENCY ANAEMIA WITH BIOIRON (International Journal of Ayurveda and Pharma Research, 2016)
AIM: To assess the efficacy and safety of BioIrontablet as a herbal iron supplement for repletion in iron deficiency anaemic patients.METHODS: Thirty subjects were evaluated in 5 sessions: screening, baseline, 14th, 28th and 56th day accompanied with a follow up assessment at least 7 days from the last visit (day 63). The efficacy parameters, such as complete blood count (CBC), red blood cell indices, erythrocyte sedimentation rate (ESR), serum iron, total iron binding capacity and serum ferritin were evaluated. Subjects were assessed using SF-36 Health Questionnaire and Fatigue Severity Scale. Safety of the investigational product was assessed by physical examination, vital signs and adverse events.RESULTS: BioIron showed a significant efficacy in 56 days as evaluated by an increase in haemoglobin (Hb) levels (p â‰¤ 0.0001) and decrease erythrocyte sedimentation rate (p â‰¤ 0.001). An increase in serum iron could be correlated to the immediate release of iron from BioIron in systemic circulation. This depicts the increased health status of subjects response to SF-36 Health Questionnaire (p â‰¤ 0.0001) and decreased fatigability (p â‰¤ 0.0001) assessed by Fatigue Severity Scale during the study course.CONCLUSIONS: Without any adverse events or serious adverse events, an appreciable statistical significance has been observed with respect to Hb level, total iron binding capacity and other laboratory parameters. Hence it can be reckoned that BioIron is safe and effective for the management of IDA.